Strategizing the Solar Energy Industry in Uzbekistan: Public-Private Partnership - Muslimakhon Sadullaeva (Strategizing: Theory and Practice, 2026)
Public-private partnerships are critical drivers of the solar energy industry in Uzbekistan. This article describes key development priorities, risks, new generating capacities, and public-private partnership mechanisms used to attract investment in this sphere. Professor V.L. Kvint’s theory of strategizing, supplemented by comparative, structural-dynamic, and institutional analyses, was applied to international and national statistics, strategies, and regulations, as well as ongoing successful solar energy projects. The article examines the current state of Uzbekistan’s energy sector, the specific features of renewable and solar energy development, national resource advantages, and the institutional conditions required for expanding private sector participation in energy projects. The accelerated development of solar energy in Uzbekistan is driven by a combination of favorable natural resource potential, state energy policy, sectoral regulatory reforms, and public-private partnership mechanisms. These partnerships serve as a key instrument for implementing large-scale solar projects by securing external financing, integrating advanced technologies, and enhancing the investment attractiveness of the sector. The findings can be used to develop public and corporate strategies, energy sector development programs, and new public-private partnership projects. Further development of solar energy in Uzbekistan requires aligning energy security objectives with infrastructure modernization, human capital development, and long-term strategic planning.